RETRACTED: Disposable Polymeric Nanostructured Plasmonic Biosensors for Cell Culture Adhesion Monitoring - Vila, Judith Camaló; Castro-Aguirre, Nerea; López-Muñoz, Gerardo A.; Ferret-Miñana, Ainhoa; De Chiara, Francesco; Ramón-Azcón, Javier (Frontiers in Bioengineering and Biotechnology, 2021)
Over the last years, optical biosensors based on plasmonic nanomaterials have gained great scientific interest due to their unquestionable advantages compared to other biosensing technologies. They can achieve sensitive, direct, and label-free analysis with exceptional potential for multiplexing and miniaturization. Recently, it has been demonstrated the potential of using optical discs as high throughput nanotemplates for the development of plasmonic biosensors in a cost-effective way. This work is a pilot study focused on the development of an integrated plasmonic biosensor for the monitoring of cell adhesion and growth of human retinal pigmented cell line (ARPE-19) under different media conditions (0 and 2% of FBS). We observed an increase of the plasmonic band displacement under 2% FBS compared to 0% conditions over time (1, 3, and 5 h). These preliminary results show that the proposed plasmonic biosensing approach is a direct, non-destructive, and real-time tool that could be employed in the study of living cells behavior and culture conditions. Furthermore, this setup could assess the viability of the cells and their growth over time with low variability between the technical replicates improving the experimental replicability.